Implementation of Prototyping Method in Web-Based POS System Development for MSMEs: A Case Study in Airmadidi District, North Sulawesi, Indonesia. - Rondonuwu , Angelly Vincentsia; Pamuji , Geraldi Catur (Proceeding of International Conference on Informatics, Engineering, Science & Technology, 2025)
This study aims to design a web-based Point of Sale (POS) system for MSMEs in Airmadidi District, North Sulawesi, Indonesia using the prototyping method. This POS system was developed to address the challenges faced by MSMEs in managing sales transactions, stock recording, and financial reporting quickly and accurately in the era of digital transformation. This study mapped user needs, designed the system interface, developed a prototype, and conducted direct evaluations with MSMEs to ensure the resulting system truly meets real-world needs. A descriptive method is employed with a prototyping approach in five stages, namely communication, quick planning, quick design, prototype development, as well as testing and feedback. The results of this study indicate that the developed POS system aligns with user needs, featuring key functionalities such as product management, sales transactions, payment processing, and data recap, all operating effectively. The system is also considered user-friendly, easy to access, and supports the operational efficiency of small and medium-scale MSMEs. The system’s relevance to user needs is achieved through iteration and direct user involvement in each phase. Thus, the application of the prototyping method provides a relevant experience and a system that is adaptive to the needs of MSMEs, while also supporting business digitalization more effectively, efficiently, and sustainably.